Teacher well-being in the classroom: A micro-longitudinal study. (July 2022) - Li, Pei-Hsin; Mayer, Diane; Malmberg, Lars-Erik
Abstract: Given the high stress and attrition rate among teachers, there is a need to expand knowledge on situational experiences that contribute to teacher well-being. We investigated the links between student lesson-specific behaviour (disruptive behaviour, engagement), teachers' lesson-specific (positive, negative) emotions, daily (morning and end-of-working), and personal general well-being of 20 Taiwanese primary school teachers using a micro-longitudinal approach. By specifying multilevel structural equation models (MSEM), we found student behaviour predicts teachers' lesson-specific emotions, and this association varied across days and teachers. Teachers' lesson-specific positive emotions predict teachers' well-being, suggesting positive emotions can be a protective factor for teachers. Highlights: Teachers reported on lessons during one calendar week. Perceived student disruptive behaviour predicted teachers' negative emotions. Perceived student engagement predicted higher positive and lower negative emotions. Lesson-specific positive emotions predicted teachers' daily and general well-being. Lesson-specific negative emotions predicted teachers' exhaustion at the day-level.